Middle Miocene climate transition in the Tibetan Plateau: identification and significance. (26th January 2022) - Song, Shijun; Huang, Lei; Zhang, Yongshu; Zhang, Qi; Zhou, Fei; Liu, Chiyang; Chen, Yan; Wu, Yingxiong; Zhang, Yiming
Abstract: The Middle Miocene Climatic Optimum is known for abrupt events during the global cooling trend of the past 20 Ma. Its identification in the Tibetan Plateau can help explain the cause of the critical Middle Miocene climate transition in Central Asia. In this study, fine-grained mixed sediments widely distributed in the Miocene Qaidam Lake in the northern Tibetan Plateau were used as a sensitive indicator for palaeoclimate. Their geochemical characteristics were investigated, together with an analysis of 2600 m long successive gamma-ray logging data from the whole JS2 drillcore, to understand the mid-Miocene climate transition in the Tibetan Plateau. By comparing the gamma-ray curve of the mixed sediments with global temperature, the Middle Miocene Climatic Optimum event can be easily identified. Further, the detailed petrological features and geochemical data of lacustrine fine-grained mixed sediments from a 400 m drillcore show oxidizing, high-sedimentation rate and brackish-saline water conditions in a semi-arid climate during the Middle Miocene period, demonstrating a dryer climate in the Qaidam Basin than in the monsoon-sensitive regions in Central Asia. These fine-grained mixed sediments have recorded climate drying before 15.3 Ma that represents a climatic transition within the Middle Miocene Climatic Optimum; increasing carbonate-rich mixed sediments, decreasing algal limestone layers and decreasing lacustrine organic matter are indicators of this transition. Regional tectonic events include the retreat of the Paratethys from Central Asia at ∼15 Ma and the synchronous tectonic reorganization of the Altyn-Tagh fault system and the northeastern Tibetan Plateau. We find that global climate change is the primary factor affecting the overall characteristics and changes of the Neogene climate in the Qaidam Basin, including the occurrence of the Middle Miocene Climatic Optimum and the cooling and drying tendency, while the regional events are a secondary factor.